The importance of Islam in the spiritual education of Kazakh youth (Eurasian Journal of Religious Studies, 2024)
These practices, which make up the spirituality of a person as a whole, are one of the most important tools with which a person becomes a Kemalat traveler, who, on the one hand, can realize the reality underlying what seems visible and invisible to the naked eye. The purpose of the article is to study how the strengthening of factors weakening the influence of religion in personal and public life with modernism, the emphasis on relativism and individualization along with postmodernism led people to turn to spiritual searches outside traditional religious structures. The idea of the scientific article is to analyze the reasons that have led to a significant number of people turning to a formal religious point of view or beginning to seek ways to realize the spiritual potential of their nature when doctrinal concepts are promoted in the interpretation and teaching of religions.The scientific direction of the research article is the study, differentiation of the spiritual potential of a person, the phenomenon of spiritualism that arose as a result of attempts to realize this potential in non-religious channels. As a result of the research, the problem and the goal are indicated by considering the need for spirituality of people and society and the responsibility of religious education in this context. Scientific significance of the article – the concept of spirituality and secondary concepts such as the meaning and kinship in the content of this concept, as well as the concepts of spirituality of Kazakh youth, two important concepts that have found their place in modern literature. The practical significance lies in the proximity of religion and spirituality in terms of origin and development; exploring the place of spirituality in religious practice and religious morality, secularism of spirituality in literature are considered.Keywords: religion, education, Kazakh youth, spirituality, teaching.